Formulasi Dan Uji Aktivitas Antioksidan Sediaan Body Scrub Ekstrak Etanol 70% Daun Salam (Syzygium Polyantum) - Sulistiyorini, Tanti; Purwanjani, Wahyu; Saraswati, Maulita (Yayasan Citra Dharma Cindekia, 2024)
Body scrub is a liquid or semi-solid dosage form in the form of an emulsion to remove dead skin cell dirt and provide skin moisture. Bay leaves (Syzygium polyantum) are also used as medicine. It is found that bay leaf extract has very strong antioxidant activity. Bay leaves contain alkaloids, flavonoids, tannins and saponins. This research carried out the formulation and antioxidant activity test of 70% ethanol extract of bay leaves with concentrations of 10%, 15% and 20%. Body Scrub was tested for antioxidants with vitamin C as a comparison. The goal this research was to find out that a body scrub with 70% ethanol extract of S. polyantum could make the skin soft and moist and improved the skin. This research was conducted experimentally. Tests in this research include organoleptic tests, pH, viscosity, homogeneity, spreadability, stickiness, and antioxidant activity tests. Bay leaf extract with concentrations of 10%, 15% and 20%. The results showed that the antioxidant activity of bay leaves according to the IC50 value showed that formula 3 has an IC50 value ranging between 177.338 ± 45.14 ppm and had a weak category value, while formula 1 and formula 2 respectively had an IC50 value of 550.25 ± 169.24 ppm; 362.07±122.08 ppm in the very weak category. The conclusion was the highest body scrub preparation formula for 70% ethanol extract of bay leaves was Formula III with a concentration of 20% with an IC50 value of 177.338 ± 45.14 ppm (weak category).